The Middleman Effect: The ethical consequences of paying others to act on one’s behalf - Macdonald, Chris (Open Science Journal, 2020)
In a time where we are increasingly made aware of unsustainable and unethical corporations, it is important to ask why consumers continue to purchase their products? Why aren't more people 'voting' with their dollar and demanding higher environmental and ethical standards? Is it simply a lack of awareness or are there also underlying factors that increase our tolerance to unethical conduct? This paper reveals a phenomenon that shares similarities to the bystander effect: the middleman effect. The results of Experiment 1 reveal that participants are more likely to purchase unethical products if there are more middlemen involved in the manufacturing process. Experiment 2 reveals that while maintaining the same number of middlemen in a given situation, it is significant when the unethical conduct takes place in a series of linear events; as the unethical conduct gets closer to the point of purchase, the tolerance of unethical behaviour decreases. The middleman effect may be an important part of the puzzle which facilitates those around the world striving for an ethical and sustainable future.